Addressing the adaptation finance gap: scaling up investment in climate change adaptation using blended finance solutions - Brown, Louis Helen (Graduate School of Business (GSB), 2023)
Climate change is a major global threat with widespread and devastating impacts for ecosystems and human livelihoods. Although efforts to reduce emissions of greenhouse gases that cause climate change are being undertaken by the international community, they fall far short of what is needed to avert catastrophic climate change. The negative impacts of climate change are disproportionately borne by the poorest communities and countries. Countries must adapt their economies and people to a warmer and less inhabitable planet. The global costs of adapting to unavoidable climate impacts could be in the region of USD 280-500 billion per year by 2050, while only about USD30 billion per year is currently being invested globally in adaptation. There is an urgent need to find ways to massively scale up funding to adapt to climate change and build the resilience of people and the ecosystems. The private sector is seen as an untapped potential for scaling up investment in adaptation, but there are a number of barriers. To unlock the private sector potential, the public sector needs to provide the enabling environment and catalytic funding to improve the risk and return profile of potential investment. Blended finance structures are of interest in this regard due to their potential to attract private investment into adaptation activities that would otherwise be perceived as too risky, by using public funds to de-risk investments. However, this is a new area of work and the literature on blended finance for adaptation is sparse, with very few empirical studies on the subject. This study sought to shed light on two research questions: i) what are the barriers to financing adaptation, for the public and private sectors? and ii) what is the role of blended finance in scaling up funding for adaptation and resilience to climate change? It used qualitative data obtained through expert interviews, as well as a case study of a blended finance facility for adaptation in the agriculture sector, to explore these questions. Based on the analysis of the responses from the expert interviews, this study identified a set of eleven barriers to scaling up adaptation finance for the public and private sectors. Three barriers relate to scaling up public sector investment in adaptation, notably i) failure on the part of developed countries to meet their climate finance pledges, leading to inadequate adaptation funding reaching developing countries, ii) failure to use public budgets strategically to finance climate change resilience, and iii) the scale of the adaptation finance challenge is beyond that which can be funded from public budgets alone. Five barriers are relevant for both public and private investment in adaptation, notably: i) issues around unclear definitions of what counts as adaptation finance, ii) lack of adequate data and metrics for tracking adaptation finance, iii) limited awareness and capacity in both the public and private sectors, iv) the economics of adaptation, which has features of public goods, and v) weak coordination, planning and institutional arrangements for scaling up adaptation finance. Three of the identified barriers are unique to private sector investment in adaptation, in particular i) difficulties in generating revenue streams from adaptation projects, ii) lack of access to concessional finance to de-risk private investments, and iii) lack of a conducive policy environment to incentivise investment. The interviews also revealed a role for blended finance in addressing the barriers for private sector investment by using public funding to enhance the revenue streams from adaptation projects, to de-risk private investment in adaptation, as well as to strengthen capacity, collect data and develop metrics for tracking adaptation projects. Blended finance approaches could include a range of instruments and interventions, such as providing enabling interventions, such as technical assistance, as well as de-risking interventions, including blended lending facilities, guarantees, junior equity, climate risk insurance and results-based finance. The study explored one such intervention through a case study of the Acumen Resilient Agriculture Fund, a blended finance approach for enhancing the resilience of the agriculture sector in several countries in East and West Africa. The Acumen Resilient Agriculture Fund demonstrates a blended finance approach whereby public concessional funding from the Green Climate Fund, by taking a first-loss equity position and providing a small amount of grant funding for capacity building, has de-risked commercial investments into an equity fund, which in turn has enabled investment into a number of small and medium sized enterprises that are supporting smallholder farmers in Kenya, Uganda, Rwanda, Nigeria, and Ghana to adopt farming practices that are more resilient to the impacts of climate change. Based on the findings of the research, the study recommends that the public sector should develop blended finance approaches that use public funds catalytically to reduce the risk or enhance the return of adaptation investments for the private sector. It also recommends that the public sector invest in awareness-raising and capacity building around adaptation for both public and private sectors; and that governments develop an enabling policy environment for private investment in adaptation.